Identifikasi Faktor-Faktor Pendorong Green Purchase Intention Terhadap Produk Bahan Bakar Di Jakarta - Ruslim, Tommy Setiawan; Dicky; Suryawan, Ian Nurpatria; Iskandar, Deni (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
As time goes by, the oil and gas industry in Indonesia continues to develop in enhancing better energy efficiency. Therefore, it is important for companies to consider factors that increase consumer purchasing intention. This research has the intent and purpose to examine whether the variables Environmental Awareness, Green Product Knowledge, Environmental Concerns and Availability affect Green Purchase Intention from XYZ fuel in Jakarta. The sampling technique in this research uses a non-probability sampling method and the type of sample used in this research is purposive sampling. In this study, questionnaires were distributed to 281 respondents who were users of motorized vehicles that use oil fuel in Jakarta and familiar with the XYZ fuel product. Data testing was carried out in this study using SmartPLS4 software. The results of this research show that Environmental Concerns do not have a positive and significant influence on Green Purchase Intention for XYZ fuel in Jakarta. Environmental Awareness, Green Product Knowledge, and Availability have a positive and significant influence on Green Purchase Intention.